2011
DOI: 10.1371/journal.pone.0021580
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling of Single Target Cell Encapsulation

Abstract: High throughput drop-on-demand systems for separation and encapsulation of individual target cells from heterogeneous mixtures of multiple cell types is an emerging method in biotechnology that has broad applications in tissue engineering and regenerative medicine, genomics, and cryobiology. However, cell encapsulation in droplets is a random process that is hard to control. Statistical models can provide an understanding of the underlying processes and estimation of the relevant parameters, and enable reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 35 publications
(65 reference statements)
5
44
0
Order By: Relevance
“…This result indicated that bioprinting did not significantly affect cell survival, which is consistent with our earlier studies. 9,33,51,52 Cells displayed typical healthy morphology generally observed in hydrogels (Figure 3B).…”
Section: Resultsmentioning
confidence: 81%
“…This result indicated that bioprinting did not significantly affect cell survival, which is consistent with our earlier studies. 9,33,51,52 Cells displayed typical healthy morphology generally observed in hydrogels (Figure 3B).…”
Section: Resultsmentioning
confidence: 81%
“…7 and Table 2). According to statistical modeling of cell encapsulation 94 and sorting 52 , the enrichment in heterogeneous cell mixtures (composed of two or more cell types) is limited by the coencapsulation probability of positive and negative cells. During the sorting step, droplets having at least one positive cell will be sorted regardless of the number of negative cells coencapsulated into the same droplet.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Moreover, a droplet has advantages to control and maintain cells within it, which allows effective handling for further processes such as separation and reactions. Encapsulation of a desired number of cells in a droplet is mainly described as a random process following Poisson’s distribution2. Although efficient ordination techniques for cell encapsulation have been reported in the literature, subsequent reactions are often needed to isolate droplets of interest345678.…”
mentioning
confidence: 99%